A Modern Perspective of Islamic Economics and Finance - Gundogdu, Ahmet Suayb (Bingley, UK : Emerald Publishing Limited, 2019)
This book aims to develop a blue print for Islamic economics and finance by starting at the grass roots of trade and commerce. It positions Islamic finance within the economic priorities of Islam while providing a cohesive understanding of Islamic economics and finance in a clear and practical manner.
Part VII: Except by Taqwa"Conclusion"; Bibliography; Appendix: To-Do List and Not-to-Do List; Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on March 01, 2019).
Master record variable field(s) change: 050
Keywords: Banks and banking -- Religious aspects -- Islam; Finance -- Religious aspects; BUSINESS & ECONOMICS / Finance; Electronic books; Electronic books